1993
DOI: 10.1007/bf01967591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH variation on the susceptibility ofHelicobacter pylori to three macrolide antimicrobial agents and temafloxacin

Abstract: The in vitro susceptibility of 27 clinical isolates of Helicobacter pylori to erythromycin, clarithromycin, azithromycin and temafloxacin under various pH conditions was evaluated. Clarithromycin (MIC90 0.03 micrograms/ml) was found to be significantly more active than either erythromycin (MIC90 0.125 micrograms/ml) or azithromycin (MIC90 0.25 micrograms/ml) at a neutral pH. Lowering the pH to 5.75 resulted in a loss in efficacy from 8- to 32-fold for all three macrolides studied. The MIC90 of clarithromycin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Evidence suggests that eradication of H. pylori is associated with faster healing and a significant decrease in peptic ulcer recurrence (18). Previous studies have demonstrated the susceptibility of H. pylori to various antibiotics or antiulcer agents (2,15,16). However, to date no single agent has consistently displayed the capability to eradicate H. pylori from the gastric and duodenal mucosa for prolonged periods of time.…”
mentioning
confidence: 99%
“…Evidence suggests that eradication of H. pylori is associated with faster healing and a significant decrease in peptic ulcer recurrence (18). Previous studies have demonstrated the susceptibility of H. pylori to various antibiotics or antiulcer agents (2,15,16). However, to date no single agent has consistently displayed the capability to eradicate H. pylori from the gastric and duodenal mucosa for prolonged periods of time.…”
mentioning
confidence: 99%
“…The treatment of gastric disease associated with H. pylon requires determination of the best therapeutic regimen by using proton pump inhibitors and antibiotics. The in vitro efficacy of clarithromycin against H. pylon (13,17,21) suggested its possible efficacy in vivo, and the results of initial clinical trials have been positive (4,11,24).…”
mentioning
confidence: 99%
“…[146,147] U sed as monotherapy, clarithromycin and its even more active 14-hydroxy metabolite proved to be the most successful of all antimicrobial compounds against H. pylori.l 112 ,1l3] The pharmacology of clarithromycin has been reviewed in depth recently.l148] Clarithromycin is more acid-stable than erythromycin, and has a high rate of absorption, independent of food administration, and reaches high tissue levels in gastric mucosa.l1 49 ] As with amoxicillin, raising the pH from 5.5 to 7.0 leads to a substantial decrease in MIC90 for the drug. [150] The excretion of all macrolides is mainly hepatobiliary, with approximately 30% being excreted via the urine. Disturbed liver function leads to increased renal excretion; dose adjustment is only necessary in patients with renal impairment.…”
Section: Macro/idesmentioning
confidence: 99%